A comparison of synthetic surfactants : evaluation of a novel surfactant (1,2-dipalmitoyl-sn-phosphatidycholine and trehalose [C12H22O11]) and comparison with other synthetic formulations - Smith, Johan (Stellenbosch : Stellenbosch University, 2012)
In title 12, 22, 11 are in subscript.